UJI EFEK DEKOKTA ANGKAK (BERAS FERMENTASI Monascus purpureus) TERHADAP KADAR TROMBOSIT TIKUS PUTIH JANTAN GALUR WISTAR TROMBOSITOPENIA YANG DIINDUKSI CISPLATIN - ., Regan Januardi Marliau (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Thrombocytopenia is the main symptom of denguehemorrhagic fever, which is still a major health problem with high morbidityand mortality rate in West Borneo. Angkak has been used empirically as amedicine to increase blood cells, particularly to increase thrombocyteObjective: The objective of this research was to understand the effect ofangkak decoction on thrombocyte in white male Wistar rat with cisplatininduced thrombocytopenia. Methods: 24 rats were divided into 6treatment groups. Thrombocytopenia was induced with single dose of 7mg/Kg BW intravenous. Phytochemical screening was performed toanalyze the content of angkak decoction. Angkak decoction was deliveredorally for 7 days. Thrombocytopenia level wan analyzed using SysmexKX-21 hematology analyzer. Result: Phytochemical screening shows thatangkak decoction contains terpenes, flavonoid, phenol, and tannin.Thrombocyte level in groups which was given angkak decoction oralydoes not have a significant difference with group which was not givenangkak decoction. Conclusion: Angkak decoction oral delivery does notincrease thrombocyte significantly in cisplatin induced thrombocytopenia inwhite male Wistar rat compared to negative control group.Key Words: Thrombocytopenia, decoction, angkak, Monascus purpureus,Sysmex KX-21 hematology analyzer Notes: 1) Medical School, Faculty of Medicine, University of Tanjungpura Pontianak, West Borneo 2) Pharmacy School, Faculty of Medicine, University of Tanjungpura Pontianak, West Borneo3) Medical School, Faculty of Medicine, University of Tanjungpura Pontianak, West Borneo